2017
DOI: 10.1188/17.cjon.93-98
|View full text |Cite
|
Sign up to set email alerts
|

Distress During Radiation Therapy: Assessment Among Patients With Breast or Prostate Cancer

Abstract: The average distress of patients with breast cancer was significantly higher than that of patients with prostate cancer, and patients with breast cancer reported more problems than those with prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
3
1
0
2
Order By: Relevance
“…The prevalence of emotional distress in the present study was lower than that in a previous study of breast cancer patients, where frequencies ranged between 15% and 46% for the six emotional problems (11). These findings were supported by the study of Stapleton et al, where the average distress of prostate cancer patients was significantly lower compared to breast cancer patients (12).…”
Section: Discussionsupporting
confidence: 78%
“…The prevalence of emotional distress in the present study was lower than that in a previous study of breast cancer patients, where frequencies ranged between 15% and 46% for the six emotional problems (11). These findings were supported by the study of Stapleton et al, where the average distress of prostate cancer patients was significantly lower compared to breast cancer patients (12).…”
Section: Discussionsupporting
confidence: 78%
“…These multimodal treatments could negatively impact the women’s well-being, as they are known to cause a lot of negative secondary effects, as described above. These differences in emotional distress observed between men and women were also reported in previous studies on depressive patients [ 74 ], cancer patients [ 68 , 75 77 ], gastroenterology patients [ 78 , 79 ] and the general population [ 80 ].…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, more reliable and robust results could be generated from the current meta-analysis compared with previous individual studies. Fourth, distress has been regarded as the sixth vital sign in the care of cancer persons (Stapleton et al, 2017;Fitch et al, 2018); however, the current meta-analysis found that limited studies evaluated the effect of the MBSR program on psychological distress of patients with lung cancer, which provides valuable implications for designing the future study. More importantly, this meta-analysis revealed that most studies were dedicated to evaluating the effectiveness of the MBSR program in physical and psychological wellbeing, but few studies tried to elucidate the potential mechanisms of the MBSR program in improving physical and psychological wellbeing.…”
Section: Discussionmentioning
confidence: 89%